VALIDATION OF THE AM5600 AMBULATORY BLOOD PRESSURE MONITOR IN CHILDREN AND ADOLESCENTS - Jones, Deborah P. (2008)
We measured ambulatory blood pressure using the AM5600 in children and adolescents participating in a research study to assess the relationship of BP to risk factors for cardiovascular disease. Although this use of this monitor has been previously reported in adults, it has not been validated in pediatric subjects. In this study, we assess the accuracy of the monitor as compared to the mercury sphygmomanometer in children ages 7-18 years of age. We found that the mean of the difference between the monitor and the mercury device was 0.29 ± 3.5 and 0.045 ± 3.7 mmHg for systolic and diastolic BP respectively, which fulfills the AAMI standard for use of a device. The cumulative percent of readings between the two devices which differed assigned the device a grade of A according to the British Hypertension Society..